Risk Mitigation as a Mandate: The Socio-Spiritual Narrative of Financing at KSPPS Artha Bahana Syariah - Ngiyanatus Sa’adah; Fuad yanuar Akhmad Rifai; M Pudail (Green Publisher Indonesia, 2025)
In the practice of Islamic microfinance, financing mitigation is one of the important instruments that has high risk because it is based on trust and profit sharing. The absence of physical security and dependence on the behavior of business partners makes risk management a crucial aspect that must be studied in depth. This study aims to analyze financing risks at KSPPS Artha Bahana Syariah Secang Branch, Magelang. Using a purely qualitative approach with an exploratory case study design, this study involved managers, financing managers, risk analysts, and cooperative members as key informants. Data collection techniques include in-depth interviews, direct observation, and analysis of internal documents of the institution. Data were analyzed through a thematic approach based on the Miles & Huberman and Braun & Clarke frameworks, to identify risk patterns and mitigation practices applied. The results of the study show that risk mitigation at KSPPS Artha Bahana Syariah Secang Branch is not only technical through SOPs and financing analysis, but also involves social and spiritual approaches. Officers interpret risk as a mandate, so they are cautious while still upholding the values of justice and empathy. Flexibility between procedures and kinship is the key to success. These findings demonstrate the importance of integration between the formal system and sharia values. Ethical training and spiritual strengthening are recommended to support the sustainability of value-based sharia cooperatives.